Osobennosti fiziologiceskogo vozdejstvija nepreryvnogo i interval'nogo metodov trenirovki na kvalificirovannych junych plovcov - Solomatin, V. R. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The present research was carried out with the aim of studying the physiological effects, the most widely used in the practice of training swimmers, continuous and interval training methods. At the same time, the individual characteristics of their functional development were taken into account. As a result, it was found that continuous swimming at a critical speed is the most effective means of increasing aerobic power in young swimmers. Continuous swimming at subcritical speed and interval swimming at critical and subcritical speeds are most conducive to the development of aerobic efficiency. The urgent training effect of the studied exercises depends on the level of individual functional capabilities of the swimmers` organism.